The criminal responsibility of the liquidators of commercial companies in Algeria - Siari, Hadjer (Journal of Human Sciences, 2023)
The expiration of the company results the ceasing of its activity and its entrance to the stage of liquidation in order to divide its assets among the partners, and this is after paying its debts. The Algerian legislator has subjected a group of companies to the provisions of liquidation, and the liquidation is supposed to end all the remaining operations of the company in order to meet its rights as well as pay its debts. If these operations result in a surplus, any net of the company’s funds, it is distributed between the partners by division, and the company’s funds are liquidated and divided in the manner indicated in the company’s contract. Accordingly, our subject here will be limited to the criminal liability of the liquidator.